DETERMINASI MODEL ALTMAN Z SCORE TERHADAP RETURN SAHAM - Mia Laksmiwati; Gresha Kosta Putri Reforma (Jurnal Akuntansi dan Keuangan, 2021)
This research goal is to determine the effect of the company's bankruptcy rate using the Altman Z-Score method on stock returns in the property and real estate sub-sector companies for the 2015-2019 period. The research population was 69 companies and the sample was 16 properties and real estates listed on the Indonesia Stock Exchange. The method used in this research is the method of Hypothesis Testing. The analytical tool used is multiple linear regression analysis tested using Statistical Package for The Social Science (SPSS) version 25. This research uses secondary data, in the form of complete financial statements during the research period. The results showed that the variables proxy by Altman Z-Score, namely Working Capital to Total Assets, Retained Earning to Total Assets, Earning Before Interest and Taxes to Total Assets, and Book Value of Equity to Book Value of Total Liabilities had a positive and significant effect on stock returns.